Konsepsi Riwayat Asbab al-Nuzul Perspektif al-Suyuti (Telaah Kitab Lubab al-Nuqul fi Asbab al-Nuzul) - Nur Ilham, Mochammad Faiz; Khulwani, Khulwani; Musafa'ah, Suqiyah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractOne of the important works in the study of Asba>b al-Nuzu>l is Luba>b al-Nuqu>l fi> Asba>b al-Nuzu>l written by al-Suyu>ti>. This article seeks to uncover the profile of his work and explore more deeply related to the conception of asba>b al-nuzu>l the perspective of Jala<l al-Di>n al-Suyu>ti> (d. 911 H), especially in his work entitled Luba>b al-Nuqu>l fi> Asba>b al-Nuzu>l. This study is important to carry out because Jala>l al-Di>n al-Suyu>ti> is considered to have a more mature conception in formulating the study of asba>b al-nuzu>l. To elaborate the problem, this research will use a descriptive-qualitative method, data taken based on literature data including scientific articles, books, books, and other scientific sources related to the research, so that this research is included in the category of library research. The results of this study show that al-Suyu>ti> carried out a theoretical-methodological development of the study of asba>b al-nuzu>l. In addition, al-Suyu>ti> also reconceptualized the study of asba>b al-nuzu>l including the understanding of asba>b al-nuzu>l, the source of obtaining of asba>b al-nuzu>l, methodological steps in formulating the asba>b al-nuzu>l, and the urgency of understanding the asba>b al-nuzu>l.Keywords: All article type, you should provide maximum 5 keyword and minimum 3 keyword, written in alphabetical, and used; AbstrakSalah satu karya penting dalam kajian Asba>b al-Nuzu>l adalah Luba>b al-Nuqu>l fi> Asba>b al-Nuzu>l yang ditulis oleh al-Suyu>ti>. Artikel ini berupaya mengungkap profil karyanya tersebut serta menelusuri lebih mendalam terkait konsepsi kajian asba>b al-nuzu>l perspektif Jala<l al-Di>n al-Suyu>ti> (w. 911 H) khususnya dalam karyanya berjudul Luba>b al-Nuqu>l fi> Asba>b al-Nuzu>l. Kajian ini penting untuk dilakukan karena Jala>l al-Di>n al-Suyu>ti> dinilai memiliki konsepsi yang lebih matang dalam merumuskan kajian asba>b al-nuzu>l. Untuk mengelaborasi permasalahan, penelitian ini akan menggunakan metode deskriptif-kualitatif, data yang diambil berbasis data kepustakaan meliputi artikel ilmiah, buku, kitab, dan sumber-sumber ilmiah lain yang berhubungan dengan penelitian, sehingga penelitian ini termasuk dalam kategori penelitian kepustakaan (library research). Hasil penelitian ini menunjukkan bahwa al-Suyu>ti> melakukan pengembangan teoritis-metodologis atas kajian asba>b al-nuzu>l. Selain itu, al-Suyu>ti> juga melakukan rekonsepsi kajian asba>b al-nuzu>l meliputi pengertian riwayat asba>b al-nuzu>l, sumber memperoleh riwayat asba>b al-nuzu>l, langkah metodologis dalam merumuskan riwayat asba>b al-nuzu>l, serta urgensitas memahami riwayat asba>b al-nuzu>l.